Land Use Change after Large Scale Disasters a Case Study of Urban Area of Ishinomaki City after the Great East Japan Earthquake. (2016) - Ubaura, Michio; Miyakawa, Masashi; Nieda, Junpei
Abstract: The recovery process from the large-scale disaster causes the diversion of land use on a large scale. It is, therefore, important to consider whether or not these changes are connected to sustainable spatial forms. This paper aims to clarify the post-Great East Japan Earthquake urban spatial transformations by investigating the diversion of agricultural land in the recovery process. The authors found that in the urban area of Ishinomaki city, land use diversion from agricultural use to urban-type was carried out mainly either in urbanization promotion areas or in urbanization restricted area collectively and orderly adjacent to UPAs. The former especially contribute to the formation of high-densely efficient urban land use. They also concluded the disorganized expansion of the urban area caused by relocation of the affected people was suppressed thanks to the both urban and agricultural land use regulation i.e. land development and land diversion regulation in URAs, established before the disaster.